Yacon Flour and Corn Steep Liquor as Substrate for Inulinase and Biomass Production by Kluyveromyces Marxianus NRRL Y-7571 - Sathler, Leonardo Amorin; Contiero, Jonas; Cazetta, Marcia Luciana (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2015)
Yacon is a perennial plant native of the Andesthat stores inulin-type polyfructans as reserve carbohydrates in its tubers. The enzymes that hydrolyze the inulin Î²-2,1 fructose linkages are called inulinases and are much used to produce high fructose syrups (HFS) and ethanol. The present study investigated inulinase and biomass production by Kluyveromyces marxianus NRRL Y-7571 using yacon flour as carbon source and corn steep liquor as nitrogen source by a Central Composite Design (CCD) 22 to carry out experiments and Surface Response Methodology (RSM) to analyze the results. The maximum enzyme production was 36.1 U.ml-1 and biomass production was 8.95 g.l-1 under the condition of 7% yacon flour and 2% corn steep liquor. The crude enzyme partial characterization showed that inulinase had optimal pH at 4.0 and optimal temperature at60°C. The enzyme maintained over 90% of its activity for four hours at45°C and50°C.